Perceptions on adolescents’ friendly health services concepts and the use of health services by adolescents in Kavango region, Namibia - Amakali-Nauiseb, Taimi; Kloppers, Joan M. (International Journal Of Community Medicine And Public Health, 2021)
Background: The objective of this study was to determine the perceptions on adolescents’ friendly health services concepts and the use of health services by adolescents in Kavango region, Namibia. Methods: A cross-sectional analytical study was conducted using mixed methods - quantitative and qualitative approaches among 350 school learners and 150 school drop-out adolescents. In total a sample of 540 was utilized. The stratified random sampling techniques were used in the selections of the circuit and the schools. Structured questionnaires were used in face-to-face interviews, and in depth interviews were conducted among the key informants (25 teachers) and as well with 15 school learners. Results: Illustrated the following: there was a statistically highly significant association between adequate confidentiality, last visit at the health facility and both sexually transmitted infections and visited health facility (p=0.004 respectively). A statistically significant association was found between all visits to health facilities, pamphlets and talks on contraceptives; visit to health facilities, comfortable and contraceptives talks (p=0.001 respectively). Additionally, there was a statistically significant association respectively between both contraceptives used and number of times services sought and between services, pamphlets and contraceptives with a (p 0.010<0.05). Conclusions: The youth need health services that are sensitive to their unique stage of biological, cognitive, and psychosocial transition into adulthood. Health services that are more accessible and acceptable to adolescents and made more youth-friendly.